Examining market synchronicity: Spillover connectedness among commodity markets and exchange rates during crisis periods - Almansour, Bashar Yaser; Shojaei, Seyed Amirhossein; Elkrghli, Sabri (Edelweiss Applied Science and Technology, 2024)
We investigate the dynamic spillover connectedness between commodity markets (gold and crude oil) and exchange rates in seven of the world's most influential developed and emerging economies: China, Ukraine, Germany, the United Kingdom, Japan, Russia, and the United States. Utilizing an extensive daily dataset sourced from Bloomberg, we analyze key exchange rates and commodity markets, focusing on currencies and economic indicators of significant global economies. Our findings reveal significant spillover effects across markets, with major currencies playing central roles in transmitting volatility during crisis periods. Specifically, currencies like EUR/$ and GBP/$ exhibit substantial internal spillovers, reflecting robust interconnectedness within these markets. In contrast, commodities such as crude oil demonstrate a more insulated nature, transmitting fewer spillovers compared to exchange rates. Furthermore, our analysis during distinct crisis periods, including the Covid-19 pandemic, the Russia-Ukraine conflict, and the Israel-Palestine war, highlights evolving market dynamics amidst geopolitical uncertainties. Major currencies continue to play pivotal roles during crises, transmitting the highest total spillovers, while commodities like gold emerge as significant transmitters and receivers, underscoring their role as safe-haven assets.